Pain: A Disease in Its Own Right - Sanjay Piplani; Monika Lalit; Niharika Piplani (Disease and Health: Research Developments Vol. 3, 2025)
Pain is a subjective perception and is an unpleasant sensory and emotional experience associated with actual or potential tissue damage. Acute Pain and Chronic Pain are the two types of pain categorized based on duration and aetiology. Acute Pain is self-limiting, indicates tissue injury, and lasts less than 30 days, whereas chronic Pain is multifactorial, progressive and associated with disability and vegetative responses and lasts longer than three months. Nociceptive pain is due to tissue injury; and the pain signalling pathway remain intact, whereas neuropathic pain is due to nerve injury and pain arises as a direct consequence of a lesion or disease affecting the somatosensory system. According to recent data from IASP and EFIC, one in five people have moderate to severe chronic pain, and one in three find it more difficult or impossible to lead an independent life as a result of their pain. Understanding whether pain is a symptom or a disease helps healthcare providers diagnose and treat the root cause effectively. It’s essential for individuals experiencing pain to seek medical advice for proper evaluation and management.